Analog-q bagi transformasi linear terhadap polinomial Rn - Murid, Ali H. M. (Department of Mathematics, Faculty of Science, 1991)
In this paper, a second q-analogue for the Rn polynomial in two variables is given. This second q-analogue is found to be equivalent with the first q-analogue of Rn discussed in the previous work. A special case of this equivalence relation is the linear transformation of the Rn polynomial.